Alaska native culture and history - International Symposium on the Culture History of the Alaska Natives, 2nd, Osaka, Japan, 1978; National Museum of Ethnology (Japan); Kotani, Yoshinobu; Workman, William B. (National Museum of Ethnology, 1978)
Incl. bibl.